Comparative Study of the Protective Effects of Citral, Thymoquinone, and Silymarin on Methotrexate-induced Cardiotoxicity in Rats - Barzan Behdokht; Noorbakhsh Mohammad Foad; Nazifi Saeed; Nasrollah Ahmadi; Amani Sakineh (Korean Pharmacopuncture Institute, 2024)
Objectives: Methotrexate (MTX), an immunosuppressant and anti-cancer medication, can harm the heart. The goal of the current investigation was to assess the cardiotoxicity caused by MTX and the potential cardioprotective properties of silymarin, citral, and thymoquinone as antioxidants.Methods: Forty-eight rats were divided into six groups, which included control, MTX, cosolvent, citral, thymoquinone, and silymarin groups. At the end of the study, the rats were anesthetized (ketamine and xylazine) and killed using CO2. Their blood samples were collected to measure the enzymatic activities of creatine kinase-myoglobin binding (CK-MB), creatine phosphokinase (CPK), and lactate dehydrogenase (LDH). Also, the heart tissue was sampled to determine the antioxidant capacity and examine the histopathology.Results: The findings revealed that the activity of CPK, CK-MB, and LDH enzymes significantly reduced in the thymoquinone treatment group compared to the MTX group (p < 0.05). On the other hand, total antioxidant capacity was significantly increased in the thymoquinone group compared to the MTX group (p < 0.05). The pathological modifications (i.e. severe congestion, edema fluid, the presence of inflammatory cells around the blood vessels, mild to moderate hemorrhaging between cardiac muscle fibers) were seen in the MTX group. The treatment groups, particularly thymoquinone, did not experience any appreciable pathological changes.Conclusion: The thymoquinone was found to have the strongest protective effect against the heart damage caused by MTX.